Circadian rhythms, athletic performance, and jet lag. Issue 2 (June 1998) - Manfredini, R; Manfredini, F; Fersini, C; Conconi, F
Abstract : Rapid air travel across several time zones exposes the traveller to a shift in his/her internal biological clock. The result is a transient desynchronisation of the circadian rhythm, called jet lag, lasting until the rhythm is rephased to the new environmental conditions. The most commonly experienced symptoms are sleep disorders, difficulties with concentrating, irritability, depression, fatigue, disorientation, loss of appetite, and gastrointestinal disturbance. Apart from the decrements in mental and physical performance directly consequent on such symptoms, competitive athletes are also exposed to the additional negative consequences of a shift from the optimal circadian window of performance. A brief summary of the possible negative effects of jet lag on athletic performance and potentially alleviating strategies is given.